Obsidian Point Discovered on Kapingamarangi Atoll, Micronesia: Implications for Post-Settlement Regional Interactions - Nagaoka, Takuya; Sheppard, Peter J.; Ross-Sheppard, Callan; Kononenko, Nina (Waka Kuaka, 2023)
An obsidian point was discovered by chance by local people on Kapingamarangi Atoll, a Polynesian Outlier in Micronesia. In addition to use-wear and residue analysis to identify its use, pXRF analysis conducted on it demonstrated that it was brought from the Admiralty Islands in Papua New Guinea over about 900 km. The information on other Admiralty obsidian artefacts found in western Oceania and other associated phenomena suggest that those artefacts were brought from the source through an interaction network between Micronesia and Melanesia during the first half of the second millennium AD. They had significant social value as prestige goods in the peripheral areas of the Admiralty obsidian circulation, serving as chiefly heirlooms and grave goods. In addition to skilful Caroline Islands seafarers, Polynesian Outlier populations had an important role in the interregional interactions during this dynamic period in the western Pacific, which was possibly activated by Polynesian intrusion into the region related to a larger Polynesian expansion into eastern Polynesia circa AD 1000. Further, we argue that the Saudeleur dynasty of Pohnpei, which achieved the development of a famous megalithic politico-religious centre, Nan Madol, was influential in the interaction sphere during its height in AD 1000–1500. Thus, by using archaeological, linguistic, historical, ethnological, oral traditional and DNA data, the interdisciplinary analysis of this rare obsidian artefact has deepened our understanding of post-settlement interaction in the region.